Zinc metal negative electrode material with Zn(002) and Zn(103) crystal surface textures and preparation method and application thereof
The crystal surface texture of Zn(002) and Zn(103) is formed in zinc metal negative electrode material by non-epitaxial electrode method, which solves the problems of zinc dendrites growth and hydrogen evolution corrosion, and improves the reversibility and cycle stability of zinc. Suitable for aqueous zinc ion batteries.
Patent Information
- Application Number
- CN202410570329.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-05-09
AI Technical Summary
The metal zinc negative electrode has problems with zinc dendrites growth and hydrogen evolution corrosion in aqueous zinc ion batteries, which hinders the commercial development of ZIBs.
By using a mixed aqueous solution of ZnSO4 and phytic acid as a texture agent, a zinc metal negative electrode material with Zn(002) and Zn(103) crystal surface texture was formed to inhibit zinc dendrites' growth and hydrogen evolution.
It achieves the inhibition of zinc dendrites, reduces hydrogen evolution and corrosion, improves the reversibility and cycle stability of zinc, and is suitable for negative electrode materials of aqueous zinc ion batteries.
Smart Images

Figure CN118480832B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of zinc negative electrode materials, and in particular to a zinc metal negative electrode material having Zn (002) and Zn (103) crystal surface textures, and a preparation method and application thereof. Background Art
[0002] Aqueous zinc-ion batteries (ZIBs) are attractive candidates for their inherent safety, low cost, and high theoretical capacity (5855 mAh cm -2 ) and other advantages, and are considered to be the next generation of energy storage batteries with great potential. However, the metal zinc negative electrode has problems such as zinc dendrite growth and hydrogen evolution and corrosion side reactions caused by the reaction between the electrolyte and zinc metal, which seriously hinder the commercial development and practical application of ZIBs. In order to alleviate the above problems, researchers have proposed many modification strategies, such as constructing surface coatings, designing new negative electrodes, modifying diaphragms and optimizing electrolytes. Among them, regulating the crystal texture of the metal zinc anode is considered to be an effective and direct method. By changing the zinc solvation structure, reforming the electric field distribution, and changing the binding energy between the substrate and zinc, the growth of zinc dendrites and hydrogen evolution can be suppressed, thereby essentially improving the reversibility of zinc.
[0003] Studies have shown that the growth of zinc dendrites is closely related to the preferential growth of specific crystal planes. The larger the angle between the crystal and the substrate, the easier it is to induce dendrite growth. If the preferred growth planes are (105), (103) and (002), the crystal grows at 0-30° to the substrate; if the preferred growth planes are (101), (102), (112) and (114), the crystal grows at 30-70° to the substrate; if the preferred growth planes are (100) and (110), the crystal grows at 70-90° to the substrate. At the same time, the researchers found through density functional theory (DFT) calculations that the binding energy between Zn atoms and the (002), (100) and (101) planes of Zn metal is different; among them, the binding energy of the (002) plane is the weakest, and the binding energy of the (101) plane is the strongest, which means that Zn atoms will preferentially deposit on this crystal plane, causing the (101) plane to grow preferentially, thus forming Zn dendrites. On the other hand, the (100) and (101) planes have higher self-diffusion barriers than the (002) plane, which limits the movement of Zn adsorbed atoms and leads to dendrite growth. Therefore, from the perspectives of kinetics and thermodynamics, the hexagonal close-packed structure of Zn has high anisotropy, which will have a negative impact on the plating / stripping process. Without regulation, there are four main arrays of Zn deposition: (1) vertical array; (2) oblique array; (3) random array; (4) horizontal array. These unfavorable arrays will accelerate the growth of Zn dendrites. It is worth noting that the preferential growth of (103) and (002) planes can form a dense deposition layer, which inhibits corrosion and H2 evolution to a certain extent. Therefore, if the (103) and (002) crystal planes can be induced to grow preferentially, the deposition layer can be made smoother and the formation of Zn dendrites can be inhibited. Therefore, reasonable regulation of crystal plane growth orientation is of great significance to inhibiting Zn dendrite growth and hydrogen evolution.
[0004] The methods for regulating the orientation of Zn crystals mainly include: physical method, chemical method, epitaxial substrate growth method, and non-epitaxial substrate growth method. However, all of the above methods have some shortcomings, such as the physical method is complex to operate and has low production efficiency; the chemical method requires the use of a large amount of chemical reagents to cause environmental pollution; the epitaxial substrate growth involves the high cost of substrate materials and the disappearance of the guiding effect when the deposition time is long. Among them, the non-epitaxial electrodeposition method has been widely studied due to its advantages of low cost, high efficiency and strong operability. Non-epitaxial substrate growth refers to the electrodeposition of Zn on untreated Zn foil, Ti foil, Cu foil and other metals with a constant voltage or constant current, and the growth of each Zn crystal plane is controlled by controlling the electrodeposition parameters such as electrodeposition time, voltage, and electrolyte. However, most of the non-epitaxial deposition reported so far is to obtain the growth of a single Zn (002) crystal plane, and there are few reports on the coordinated growth of two or more crystal planes to suppress zinc dendrites, hydrogen evolution and corrosion problems to improve the reversibility of zinc. Summary of the invention
[0005] In view of the deficiencies in the above-mentioned prior art, the present invention provides a zinc metal negative electrode material having Zn (002) and Zn (103) crystal plane textures, and a preparation method and application thereof. The present invention adopts a mixed aqueous solution of ZnSO4 and phytic acid as a texturing agent, and textures the surface of metallic zinc by a non-epitaxial electrodeposition method to obtain zinc metal having (002) and (103) crystal plane textures, and uses it as a negative electrode material. The preparation method of the present invention has a simple process, low cost, and can be mass-produced. The zinc metal negative electrode material prepared by the present invention is used as a negative electrode material for aqueous zinc ion batteries, which can effectively inhibit the growth of zinc dendrites and side reactions on the negative electrode surface, thereby exhibiting excellent cycle stability.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] A method for preparing a zinc metal negative electrode material having Zn (002) and Zn (103) crystal surface textures comprises the following steps:
[0008] In a texturing agent, a zinc foil is used as a working electrode, and a deposition layer is formed on the surface of the zinc foil by a non-epitaxial deposition method, thereby obtaining a zinc metal negative electrode material having a Zn (002) and Zn (103) crystal surface texture;
[0009] The texturing agent is a mixed aqueous solution of ZnSO4 and phytic acid.
[0010] Preferably, the concentration of phytic acid is 0.1 to 0.9 mol / L; further, the concentration of phytic acid is 0.4 to 0.8 mol / L.
[0011] Preferably, the concentration of ZnSO4 is 0.5 to 3 mol / L; further, the concentration of ZnSO4 is 1 to 2 mol / L.
[0012] Preferably, the steps of the non-epitaxial deposition method are:
[0013] A three-electrode system was constructed with polished zinc foil as the working electrode, platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and texturing agent as the electrolyte.
[0014] The non-epitaxial electrodeposition was carried out by chronoamperometry to form a deposition layer on the surface of the working electrode, thereby obtaining a zinc metal negative electrode material having Zn (002) and Zn (103) crystal plane textures.
[0015] Preferably, the deposition voltage is -1.3 to -1.8 V, and the deposition time is 5 to 90 min; further, the deposition voltage is -1.4 to -1.6 V, and the deposition time is 15 to 25 min.
[0016] Preferably, the zinc foil has a purity of >99.99% and a thickness of 50 μm.
[0017] The present invention also protects the zinc metal negative electrode material with Zn (002) and Zn (103) crystal surface textures obtained by the above preparation method.
[0018] The present invention also protects the use of zinc metal negative electrode materials with Zn (002) and Zn (103) crystal surface textures in the preparation of aqueous zinc ion batteries.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The present invention uses a non-epitaxial electrodeposition method to texture a Zn foil with two advantageous crystal planes growing synergistically, specifically Zn (002) and Zn (103) crystal plane textures, so as to jointly inhibit zinc dendrites, hydrogen evolution and corrosion through the coordinated growth of each crystal plane, thereby improving the reversibility of zinc.
[0021] 2. The present invention adopts a phytic acid-assisted non-epitaxial deposition strategy, uses a mixed aqueous solution of ZnSO4 and phytic acid as a texturing agent, and optimizes the deposition kinetics of the zinc negative electrode surface by regulating the deposition voltage and time parameters, thereby achieving the coordinated growth of Zn(002) and Zn(103);
[0022] The principle of phytic acid textured crystal face growth is: phytic acid is an organic acid containing 6 phosphate carboxyl groups and 12 hydroxyl groups, which can produce strong chelation with zinc ions to form a phytic acid-zinc metal complex. On the one hand, this can generate an interfacial protective layer in situ on zinc metal, which can optimize the deposition kinetics of the zinc negative electrode surface and inhibit the occurrence of dendrite growth and surface side reactions; on the other hand, the phytic acid-zinc metal complex preferentially and selectively adsorbs on the Zn (002) crystal plane to form a dynamic protective layer, thereby inducing the growth of the (103) crystal face.
[0023] ZnSO4 solution is a commonly used electrolyte in aqueous zinc-ion batteries, which mainly obtains (002) crystal plane texture. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 XRD diagrams of the zinc metal negative electrode material with Zn(002) and Zn(103) crystal plane textures in Example 1, the zinc metal negative electrode material with Zn(002) crystal plane texture in Comparative Example 1, and the zinc metal negative electrode material with Zn(103) crystal plane texture in Comparative Example 2;
[0025] Figure 2 The surface SEM image of the zinc metal negative electrode material with Zn(002) and Zn(103) crystal plane textures of Example 1;
[0026] Figure 3This is a cycle performance diagram of a Zn||Zn symmetric battery assembled using the zinc metal negative electrode material with Zn(002) and Zn(103) crystal plane textures of Example 1;
[0027] Figure 4 In the figure, (a) is a linear sweep voltammetric curve of the zinc metal negative electrode material with Zn (002) and Zn (103) crystal plane textures of Example 1; (b) is an IV curve under the condition of lower than the over-limit voltage -1.5V; (c) is an IV curve under the condition of over-limit voltage -2.2V; (d) is an optical photograph under the condition of lower than the over-limit voltage -1.5V; (e) is an optical photograph under the condition of over-limit voltage -2.2V;
[0028] Figure 5 Among them, (a) is the XRD diagram under the condition of phytic acid concentration of 0.1-0.9 mol / L; (b) is the XRD diagram under the electrodeposition voltage of -1.3V~-1.6V; (c) is the XRD diagram under the electrodeposition voltage of -1.7V~-2.0V; (d) is the XRD diagram under the electrodeposition voltage of -1.58V~-1.64V; (e) is the XRD diagram under the electrodeposition time of 15-25min; (f) is the optical photograph under the conditions of ZnSO4 concentration of 1 mol / L, phytic acid concentration of 0.5 mol / L, electrodeposition voltage of -1.6V, and electrodeposition time of 20min. DETAILED DESCRIPTION
[0029] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.
[0030] The present invention uses ZnSO4 solution as an electrolyte, and then mixes phytic acid with the ZnSO4 solution to obtain a texturing agent. The texturing agent is used as an electrolyte to form a deposition layer on the surface of the zinc foil, thereby obtaining a zinc metal negative electrode material with preferential growth of (103) and (002) planes. In the zinc metal negative electrode material with Zn (002) and Zn (103) crystal plane textures, a dense deposition layer is formed on the surface of the zinc foil, and not only is the deposition layer smooth, but the smooth deposition layer also inhibits the formation of Zn dendrites, and at the same time inhibits corrosion and H2 precipitation to a certain extent, thereby showing excellent cycle stability.
[0031] In addition, the present invention also screens the phytic acid concentration, deposition voltage and time parameters to obtain the best electrodeposition conditions, and then obtains a dense deposition layer on the surface of the zinc foil to overcome the technical defects of the zinc foil in the prior art.
[0032] The technical solution of the present invention is further explained by using embodiments below, which are specifically as follows:
[0033] Example 1
[0034] A method for preparing a zinc metal negative electrode material having Zn (002) and Zn (103) crystal surface textures comprises the following steps:
[0035] S1. First, use fine sandpaper to polish the high-purity zinc foil (99.99%), then use ethanol and acetone to ultrasonically clean it, and then blow it dry with nitrogen;
[0036] S2, prepare a mixed aqueous solution of ZnSO4 and phytic acid as an electrolyte, the concentration of phytic acid in the electrolyte is 0.5 mol / L, the concentration of ZnSO4 is 1 mol / L, and put zinc foil into the electrolyte as a working electrode, platinum mesh as a counter electrode, Ag / AgCl as a reference electrode, and assemble into a three-electrode system;
[0037] S3. At room temperature, non-epitaxial electrodeposition of zinc foil was performed by chronoamperometry, with the deposition voltage set to -1.6 V, the deposition time set to 20 min, and the protective atmosphere set to nitrogen;
[0038] S4, taking out the textured zinc negative electrode after non-epitaxial electrodeposition, washing it with ethanol and distilled water three times, and then drying it at room temperature under a protective atmosphere to obtain a zinc metal negative electrode material with Zn (002) and Zn (103) crystal plane textures;
[0039] The (002) and (103) plane texture strengths of the zinc foil after electrodeposition are 9.8 and 10.2, respectively.
[0040] Example 2
[0041] A method for preparing a zinc metal negative electrode material having Zn (002) and Zn (103) crystal surface textures comprises the following steps:
[0042] S1. First, use fine sandpaper to polish the high-purity zinc foil (99.99%), then use ethanol and acetone to ultrasonically clean it, and then blow it dry with nitrogen;
[0043] S2, prepare a mixed aqueous solution of ZnSO4 and phytic acid as an electrolyte, the concentration of phytic acid in the electrolyte is 0.3 mol / L, the concentration of ZnSO4 is 1 mol / L, and put zinc foil into the electrolyte as a working electrode, platinum mesh as a counter electrode, Ag / AgCl as a reference electrode, and assemble into a three-electrode system;
[0044] S3. At room temperature, the zinc foil was subjected to non-epitaxial electrodeposition by chronoamperometry, with the deposition voltage set to -1.6 V, the deposition time set to 20 min, and the protective atmosphere set to nitrogen;
[0045] S4, taking out the textured zinc negative electrode after non-epitaxial electrodeposition, washing it with ethanol and distilled water three times, and then drying it at room temperature under a protective atmosphere to obtain a zinc metal negative electrode material with Zn (002) and Zn (103) crystal plane textures;
[0046] The (002) and (103) plane texture strengths of the zinc foil after electrodeposition are 0.6 and 1.1, respectively.
[0047] Example 3
[0048] A method for preparing a zinc metal negative electrode material having Zn (002) and Zn (103) crystal surface textures comprises the following steps:
[0049] S1. First, use fine sandpaper to polish the high-purity zinc foil (99.99%), then use ethanol and acetone to ultrasonically clean it, and then blow it dry with nitrogen;
[0050] S2, preparing a mixed aqueous solution of ZnSO4 and phytic acid as an electrolyte, wherein the concentration of phytic acid in the electrolyte is 0.5 mol / L, and the concentration of ZnSO4 is 1 mol / L, and putting zinc foil into the electrolyte as a working electrode, a platinum mesh as a counter electrode, and Ag / AgCl as a reference electrode to assemble into a three-electrode system;
[0051] S3. At room temperature, non-epitaxial electrodeposition of zinc foil was performed by chronoamperometry, with the deposition voltage set to -1.4 V, the deposition time set to 20 min, and the protective atmosphere set to nitrogen;
[0052] S4, taking out the textured zinc negative electrode after non-epitaxial electrodeposition, washing it with ethanol and distilled water three times, and then drying it at room temperature under a protective atmosphere to obtain a zinc metal negative electrode material with Zn (002) and Zn (103) crystal plane textures;
[0053] The (002) and (103) plane texture strengths of the zinc foil after electrodeposition are 1.9 and 3.4, respectively.
[0054] Comparative Example 1
[0055] The preparation method of the zinc metal negative electrode material having a Zn (002) crystal surface texture is the same as the preparation steps of Example 1, except that the electrolyte is only a ZnSO4 solution, and includes the following steps:
[0056] S1. First, use fine sandpaper to polish the high-purity zinc foil (99.99%), then use ethanol and acetone to ultrasonically clean it, and then blow it dry with nitrogen;
[0057] S1. Prepare 1 mol / L ZnSO4 solution as electrolyte, use zinc foil as working electrode, platinum mesh as counter electrode, and Ag / AgCl as reference electrode to assemble into a three-electrode system;
[0058] S2. At room temperature, the zinc foil was subjected to non-epitaxial electrodeposition by chronoamperometry, with the deposition voltage set to -1.6 V, the deposition time set to 20 min, and the protective atmosphere set to nitrogen;
[0059] S3, after non-epitaxial electrodeposition, the textured zinc negative electrode was taken out, washed with ethanol and distilled water three times, and then dried at room temperature under a nitrogen atmosphere to obtain a zinc metal negative electrode material with a Zn (002) crystal plane texture;
[0060] After electrodeposition treatment, the zinc foil only showed (002) crystal plane enhancement, and the texture strength was 1.4.
[0061] Comparative Example 2
[0062] The preparation method of the zinc metal negative electrode material having the Zn (103) crystal surface texture is the same as the preparation steps of Example 1, except that the electrolyte is only a phytic acid solution, and comprises the following steps:
[0063] S1. First, use fine sandpaper to polish the high-purity zinc foil (99.99%), then use ethanol and acetone to ultrasonically clean it, and then blow it dry with nitrogen;
[0064] S2, prepare 0.5 mol / L phytic acid solution as electrolyte, and assemble into a three-electrode system with zinc foil as working electrode, platinum mesh as counter electrode, and Ag / AgCl as reference electrode;
[0065] S3. At room temperature, the zinc foil was subjected to non-epitaxial electrodeposition by chronoamperometry, with the deposition voltage set to -1.6 V, the deposition time set to 20 min, and the protective atmosphere set to nitrogen;
[0066] S4. After non-epitaxial electrodeposition, the textured zinc negative electrode was taken out, washed three times with ethanol and distilled water, and then dried at room temperature under a nitrogen atmosphere to obtain a zinc metal negative electrode material with a Zn (103) crystal surface texture.
[0067] After electrodeposition treatment, the zinc foil only showed (103) crystal plane enhancement, and the texture strength was 2.0.
[0068] In Examples 1-3 of the present invention, zinc metal negative electrode materials with Zn (002) and Zn (103) crystal surface textures are prepared. The zinc metal negative electrode material of Example 1 is used as an example for research. The specific research method and results are as follows:
[0069] like Figure 1As shown in the figure, compared with the untextured pure zinc sheet, the (002) crystal plane peak of the zinc negative electrode textured in 1mol / L ZnSO4 solution is significantly enhanced, and the (103) crystal plane diffraction peak of the zinc negative electrode textured in 0.5mol / L phytic acid solution is enhanced, which shows that a single electrolyte can only achieve the growth of a specific dominant crystal plane in a targeted manner. In the mixed electrolyte system of 1mol / L ZnSO4 and 0.5mol / L phytic acid, the voltage is adjusted to -1.6V, and the signal peaks of the (002) and (103) crystal planes on the surface of the textured zinc negative electrode are both enhanced, which indicates that the coordinated growth of the (002) and (103) crystal planes is achieved in this system.
[0070] like Figure 2 As shown, from the SEM image of the zinc negative electrode surface after texturing, it is also possible to observe the (002) and (103) crystal planes of obvious hexagonal close-packed structure, which is consistent with the XRD results.
[0071] like Figure 3 As shown, when the electrodeposition voltage is adjusted to -1.6 V and the electrodeposition time is 20 min, the (002) and (103) crystal planes on the zinc negative electrode surface have the strongest characteristics, and the RTCs are 9.8 and 10.2, respectively.
[0072] The following adopts the assembly of Zn||Zn symmetric battery to further study the electrochemical performance through Zn||Zn symmetric battery. The assembly method of the battery is:
[0073] The battery shell was ultrasonically cleaned 2 to 3 times in a beaker containing water and ethanol, and the cleaned battery shell was dried in an oven at 60°C;
[0074] The positive and negative Zn sheets are cut into small discs with a diameter of 2.8 cm using a punching machine, and the glass fiber separator is cut into small discs with a diameter of 3 cm; the positive and negative Zn are the same, and are selected from the zinc metal negative electrode material with Zn (002) crystal surface texture of Example 1 of the present invention;
[0075] As a blank control group, the polished pure zinc sheet (untextured) was also used as the positive and negative electrodes to assemble symmetrical batteries and compared with the battery assembled with the textured zinc sheet;
[0076] Prepare 1 mol / L ZnSO4 solution and assemble the battery. The assembly order is stacked from bottom to top and the electrolyte is injected: negative electrode shell → spring → gasket → metal zinc sheet → diaphragm → 100 μL electrolyte → metal zinc sheet → positive electrode shell to obtain a Zn||Zn symmetrical battery;
[0077] The zinc foil prepared in Example 1 was directly used as an electrode to assemble a Zn||Zn symmetric battery for electrochemical performance testing. Thanks to the synergistic growth of Zn(002) and Zn(103), the prepared zinc metal negative electrode material exhibited excellent electrochemical reversibility and cycle stability at 2 mA / cm 2 and 2mAh / cm 2 Under the test conditions, the symmetrical battery can operate stably for more than 2500h with an overpotential of only 50mV.
[0078] The zinc foil prepared in Example 2 was directly used as an electrode to assemble a Zn||Zn symmetrical battery for electrochemical performance testing, which showed excellent cycle stability at 2 mA / cm 2 and 2mAh / cm 2 Under the test conditions, the symmetrical battery can operate stably for more than 2000 hours, and the overpotential is only about 60mV.
[0079] The zinc foil prepared in Example 3 was directly used as an electrode to assemble a Zn||Zn symmetric battery for electrochemical performance testing, which showed excellent cycle stability at 2 mA / cm 2 and 2mAh / cm 2 Under the test conditions, the symmetrical battery can operate stably for more than 1800 hours, and the overpotential is only about 80mV.
[0080] The zinc foil prepared in Comparative Example 1 was directly used as an electrode to assemble a Zn||Zn symmetric battery for electrochemical performance testing. 2 and 2mAh / cm 2 Under the test conditions, it can only cycle for 800 hours.
[0081] The zinc foil prepared in Comparative Example 2 was directly used as an electrode to assemble a Zn||Zn symmetric battery for electrochemical performance testing. 2 and 2mAh / cm 2 Under the test conditions, it can only cycle for 1000h.
[0082] Studies have shown that the electrodeposition voltage is closely related to the Zn texture morphology, and a dense and uniform texture morphology must be produced under conditions below the limiting voltage (VL). The limiting voltage is the threshold that limits the diffusion of electrodeposition, and the precise limiting voltage is obtained through the linear sweep voltammetry (LSV) curve. Therefore, we conducted an LSV test on it. Figure 4 (a) It can be seen that the V measured in the 1 mol / L ZnSO4 + 0.5 mol / L phytic acid electrolyte system L ≈-1.88V.
[0083] The present invention also studies the electrodeposition behavior under the condition of over-limit voltage (-2.2V) and under the condition of lower than over-limit voltage (-1.5V), such as Figure 4 (b) and Figure 4 (c) shows that, below the over-limit voltage ( Figure 4 (b)) Zinc electrocrystallization starts at a high nucleation current density and then stabilizes at a current density for nucleation growth. Under this condition, the ion concentration quickly reaches a stable state and presents a constant concentration gradient from the bulk solution to the electrode surface. Ion diffusion follows Fick's first law. In the case of excess electrolyte, the zinc surface ion concentration will not drop to zero as the electrodeposition time increases. Under over-limit conditions ( Figure 4 (c)), the continuous decrease in ion concentration near the electrode surface will cause the current density to continue to increase after zinc nucleation is completed. Then, through optical photography ( Figure 4 (d) and Figure 4 (e)) The morphology of Zn foil after non-epitaxial electrodeposition under overvoltage (-2.2V) and under overvoltage (-1.5V) was characterized. The results show that under the condition of undervoltage (-1.5V), the surface of the deposited Zn foil is uniform and fine. In contrast, the surface of the Zn foil deposited under overvoltage (-2.2V) is rough and bumpy. Similarly, the SEM image also confirms this. Under the condition of undervoltage (-1.5V), the deposited Zn is uniform and fine, with small grains. On the contrary, the Zn grains deposited under overvoltage (-2.2V) are large and uneven. Therefore, the subsequent electrodeposition voltage is set to be electrodeposited under the condition of undervoltage (-1.5V).
[0084] The present invention also determines the optimal conditions for the coordinated growth of textured Zn (002) and Zn (103) crystal planes, as follows:
[0085] (1) Effect of different phytic acid concentrations on the synergistic growth of electrodeposited Zn(002) and Zn(103) crystal planes:
[0086] The I(002) / I(101) and I(103) / I(101) peak intensity ratios are important indicators for judging the effect of electrodeposition on obtaining Zn(002) and Zn(103) crystal planes. At the same time, based on the relationship between the above-mentioned electrodeposition voltage and the textured Zn morphology, in order to obtain the coordinated growth of Zn(002) and Zn(103) crystal planes with strong diffraction texture, the effect of different phytic acid concentrations on the coordinated growth of electrodeposited Zn(002) and Zn(103) crystal planes was first investigated, and experiments with phytic acid concentrations of 0.1 mol / L, 0.3 mol / L, 0.5 mol / L, 0.7 mol / L, and 0.9 mol / L were designed, and the concentration of ZnSO4 was 1 mol / L. Under the conditions of the electrodeposition voltage of -1.6 V and the time of 15 min, the XRD patterns of phytic acid of different concentrations are shown in the figure below. Figure 5 As shown in (a), when the phytic acid concentration is 0.5 mol / L, the peak intensity ratios of I(002) / I(101) and I(103) / I(101) reach the maximum. At this concentration, the electrodeposition texture Zn(002) and Zn(103) crystal plane growth effects are the best, so the subsequent screening of other conditions is carried out using phytic acid with a concentration of 0.5 mol / L.
[0087] (2) Effect of electrodeposition voltage on the coordinated growth of Zn(002) and Zn(103) crystal planes under conditions below the overvoltage limit:
[0088] A series of experiments were designed with electrodeposition voltages of -1.30V, -1.40V, -1.50V, -1.58V, -1.60V, -1.62V, -1.64V, -1.70V, -1.80V, -1.90V, and -2.0V, respectively. At this time, the concentration of ZnSO4 was 1 mol / L, and the electrodeposition time was 15 min. The XRD patterns of 0.5 mol / L phytic acid at different electrodeposition voltages are shown in the figure below. Figure 5 As shown in (b)-5(d), the results show that when the electrodeposition time is 15 minutes and the electrodeposition voltage is -1.6 V, the peak intensity ratios of I(002) / I(101) and I(103) / I(101) reach the maximum, which are 1.8 and 3.4 respectively. Under this condition, the electrodeposition texture Zn(002) and Zn(103) crystal plane growth effects are the best.
[0089] (3) Effect of electrodeposition time on the coordinated growth of Zn(002) and Zn(103) crystal planes:
[0090] A series of experiments with electrodeposition time of 15min, 20min, and 25min were designed. At this time, the concentration of ZnSO4 was 1mol / L, the concentration of phytic acid was 0.5mol / L, and the electrodeposition voltage was -1.6V. The XRD patterns of 0.5mol / L phytic acid at different electrodeposition voltages and times are shown in Figure 2. Figure 5As shown in (e), the results show that when the electrodeposition voltage is -1.6 V and the electrodeposition time is 20 min, the peak intensity ratios of I(002) / I(101) and I(103) / I(101) reach the maximum, which are 4.9 and 5.1 respectively. Under this condition, the electrodeposition texture Zn(002) and Zn(103) crystal plane growth effects are the best.
[0091] At the same time, optical photos such as Figure 5 (f) Figure 5 (f) also shows that when the concentration of ZnSO4 is 1 mol / L, the concentration of phytic acid is 0.5 mol / L, the electrodeposition voltage is -1.6 V, and the electrodeposition time is 20 min, the surface of the deposited Zn foil is uniform and fine. In summary, the optimal conditions for the coordinated growth of Zn (002) and Zn (103) crystal planes in non-epitaxial electrodeposition texture are 0.5 mol / L phytic acid, the electrodeposition voltage is -1.6 V, and the electrodeposition time is 20 min.
[0092] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalent technologies, the present invention is also intended to include these changes and variations. The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and their protection scope is not limited thereto. Equivalent substitutions or changes made by those skilled in the art on the basis of the present invention are all within the protection scope of the present invention, and the protection scope of the present invention shall be subject to the claims.
Claims
1. A method for preparing a zinc metal negative electrode material having Zn (002) and Zn (103) crystal surface textures, characterized in that: The steps include: In a texturing agent, a zinc foil is used as a working electrode, and a deposition layer is formed on the surface of the zinc foil by a non-epitaxial deposition method, thereby obtaining a zinc metal negative electrode material having a Zn (002) and Zn (103) crystal surface texture; The texturing agent is a mixed aqueous solution containing ZnSO4 and phytic acid; The steps of the non-epitaxial deposition method are: A three-electrode system was constructed with zinc foil as the working electrode, platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and texturing agent as the electrolyte. The non-epitaxial electrodeposition is carried out by using the chronoamperometry method to form a deposition layer on the surface of the working electrode, thereby obtaining a zinc metal negative electrode material having Zn (002) and Zn (103) crystal surface textures; The deposition voltage of non-epitaxial electrodeposition is -1.3 to -1.8 V, and the deposition time is 5 to 90 minutes.
2. The method for preparing a zinc metal negative electrode material having Zn (002) and Zn (103) crystal surface textures according to claim 1, characterized in that: The concentration of phytic acid is 0.1~0.9 mol / L.
3. The method for preparing a zinc metal negative electrode material having Zn(002) and Zn(103) crystal surface textures according to claim 2, characterized in that: The concentration of phytic acid is 0.4-0.8 mol / L.
4. The method for preparing a zinc metal negative electrode material having Zn(002) and Zn(103) crystal surface textures according to claim 1, characterized in that: The concentration of ZnSO4 is 0.5~3mol / L.
5. The method for preparing a zinc metal negative electrode material having Zn (002) and Zn (103) crystal surface textures according to claim 1, characterized in that: The deposition voltage of non-epitaxial electrodeposition is -1.4 to -1.6 V, and the deposition time is 15 to 25 minutes.
6. The method for preparing a zinc metal negative electrode material having Zn(002) and Zn(103) crystal surface textures according to claim 1, characterized in that: The purity of zinc foil is >99.99% and the thickness is 50μm.
7. A zinc metal negative electrode material having Zn(002) and Zn(103) crystal surface textures obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the zinc metal negative electrode material having Zn(002) and Zn(103) crystal surface textures as claimed in claim 7 in an aqueous zinc ion battery.
Citation Information
Patent Citations
Preparation method for zinc metal with certain crystal face orientation through phosphorus-containing organic acid electro-deposition
CN117071003A